2003
DOI: 10.1159/000078156
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Understanding GJB2-Linked Deafness

Abstract: Mutations in the GJB2 gene (encoding for Connexin 26 protein) represent a leading cause of genetic hearing impairment. Extensive epidemiological and molecular studies have been reported, describing GJB2 mutations type, frequency and distribution. Moreover, several aspects of GJB2 mutations pathogenic effects have been elucidated taking advantage of in vitro and in vivo experimental approaches. Progress through reported studies is reviewed, highlighting recent major achievements in this field. Attention is focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(63 reference statements)
0
3
1
Order By: Relevance
“…The data from the two sperm banks showed that 18.6% and 14.4% of qualified sperm donors in China were carriers of pathogenic variants of GJB2. This is higher than the carrier frequencies for GJB2 that were previously reported ( 15 , 16 ). However, this is not surprising, as previous studies on carrier frequencies tested for known mutations, whereas the exome sequencing at these two clinics explored the entire coding region of most genes.…”
Section: Discussioncontrasting
confidence: 55%
“…The data from the two sperm banks showed that 18.6% and 14.4% of qualified sperm donors in China were carriers of pathogenic variants of GJB2. This is higher than the carrier frequencies for GJB2 that were previously reported ( 15 , 16 ). However, this is not surprising, as previous studies on carrier frequencies tested for known mutations, whereas the exome sequencing at these two clinics explored the entire coding region of most genes.…”
Section: Discussioncontrasting
confidence: 55%
“…A perturbation of this protein product may cause alterations in the potassium homeostasis within the cell and results in cell death and subsequent deafness [20]. This pathophysiology would suggest that the effect of a cochlear implant to stimulate the auditory nerve would be successful and contribute to spoken language development.…”
Section: Discussionmentioning
confidence: 99%
“…Non-syndromic deafness is a partial or total loss of hearing that is not associated with other pathologies, and occurs in ~1 in 1000 newborn children. Cx26 mutations contribute to ~50% of genetic deafness and hearing loss can range from mild to profound, be stable or progressive, and impact different sound frequencies [32, 33]. An abundance of data suggests that either partial or total loss of function mutations in Cx26 contribute to non-syndromic deafness [34, 35].…”
Section: Human Disorders Caused By Connexin Mutationsmentioning
confidence: 99%